Imperialism and Contemporary Global Capitalism: China, Russia and the US - Harris, Jerry (Revista de Estudios Globales. Análisis Histórico y Cambio Social, 2024)
The nature of imperialism has changed over the past 45 years of globalization. The global capitalist system still retains important aspects of state-centric politics and the Western hierarchy but the vast integration of transnational finance and networked production has reshaped relationships and links the big bourgeoise of all countries. The contradictions between the older imperialist system of states, first articulated by Lenin and others of his generation, and contemporary forms of neoliberal domination has created a complex situation of contending forces and influence. The article explores these questions by examining the US/China relationship, and the Russian invasion of Ukraine.